PENGARUH SOCIAL MEDIA USE TERHADAP INTRINSIC MOTIVATION PADA TARUNA POLITEKNIK ILMU PEMASYARAKATAN - Rachmayanthy; Rieza Irfan Maulana (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2024)
The use of social media in Indonesia, especially amongthose of productive age who are still receiving education,is increasing, this is proven by the 276 million populationin Indonesia, social media users reach 60% of the totalpopulation. This also happens to the Correctional SciencesPolytechnic Cadets, who on average already have socialmedia accounts. However, the consequences are studentsfailing to graduate in academics and disciplinaryviolations. This phenomenon prompted research todetermine the influence of social media use on intrinsicmotivation of Correctional Science Polytechnic Cadets andtheir perceptions of each of these variables. This researchis quantitative research using a survey method via GoogleForm. This research sample was taken using a nonprobability purposive or judgment sampling techniquewhich refers to the Krejcie and Morgan sample table,obtaining 181 samples. Data analysis in this research wascarried out using IBM SPSS version 27 software.Hypothesis test results show that the use of social mediahas a significant positive influence on the intrinsicmotivation of Correctional Science Polytechnic Cadets andthe perception of each of these variables shows quite goodresults. Thus, this research has important implications inincreasing intrinsic motivation for Correctional SciencePolytechnic Cadets which has an impact on improvementsin discipline and academic fields.